Severity dependent distribution of impairments in PSP and CBS: Interactive visualizations. (March 2019) - Brittain, Claire; McCarthy, Andrew; Irizarry, Michael C.; McDermott, Dana; Biglan, Kevin; Höglinger, Günter U.; Lorenzl, Stefan; del Ser, Teodoro; Boxer, Adam L.; ,; ,; ,; et al.
Abstract: Background: Progressive supranuclear palsy (PSP) -Richardson's Syndrome and Corticobasal Syndrome (CBS) are the two classic clinical syndromes associated with underlying four repeat (4R) tau pathology. The PSP Rating Scale is a commonly used assessment in PSP clinical trials; there is an increasing interest in designing combined 4R tauopathy clinical trials involving both CBS and PSP. Objectives: To determine contributions of each domain of the PSP Rating Scale to overall severity and characterize the probable sequence of clinical progression of PSP as compared to CBS. Methods: Multicenter clinical trial and natural history study data were analyzed from 545 patients with PSP and 49 with CBS. Proportional odds models were applied to model normalized cross-sectional PSP Rating Scale, estimating the probability that a patient would experience impairment in each domain using the PSP Rating Scale total score as the index of overall disease severity. Results: The earliest symptom domain to demonstrate impairment in PSP patients was most likely to be Ocular Motor, followed jointly by Gait/Midline and Daily Activities, then Limb Motor and Mentation, and finally Bulbar. For CBS, Limb Motor manifested first and ocular showed less probability of impairment throughout the disease spectrum. An online tool to visualize predicted disease progression was developed to predict relative disability on each subscale per overall disease severity. Conclusion: The PSP Rating Scale captures disease severity in both PSP and CBS. Modelling how domains change in relation to one other at varying disease severities may facilitate detection of therapeutic effects in future clinical trials. Highlights: PSP Rating Scale captures overall disease and domain severity in both PSP and CBS. Using large body of existing data gives robust characterization of disease spectrum. Modelled online tool may facilitate detection of therapeutic effects. Online toolhttps://pspmodel.shinyapps.io/PSP_Progression/ .